Interfaith Marriage Between Sunni And Shia: A Phenomenological Study In The Bondowoso Arab Community - Musdhalifah, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
This study aims to analyze phenomenologically related to the phenomenon of marriage across streams, between Sunnis and Shi'a, who have been known to have striking differences in beliefs. The difference is not only related to furu'iyah matters, but also related to things that are akidah. But in the Arab Community in Bondowoso has a unique phenomenon that makes Sunnis and Shi'a coexist, even holding marriages between them in order to become a strong familial relationship. This research uses a qualitative-based field research approach. The method used for the analysis of researchers used the phenomenological method of transendental Edmund Hurssel. This method researchers use to explain the meaning "as it is" in the phenomenon of marriage in the Arab Community. The study found: In the community of bondowoso Shi'a and Sunni Bondowoso Arab communities although they have differences in terms of faith and harmony Islam, but the attitude of tolerance (Tasamuh), precisely to affirm this they use marriage ties. Nevertheless, tensions are precisely in the territory of the elite religious organizations CENTRAL MUI and MUI Bondowoso. Differences of opinion between the Majelis Ulama Indonesia (MUI) on the fatwa of misguidance of Syi'ah by MUI JATIM, NO: Kep-01 / SKF-MUI / JTM / I / 2012 and the views of the Indonesian Ulema Council (MUI) Bondowoso which does not consider Shia heresy in Bondowoso.